Properties of bacteriorhodopsin derivatives constructed by insertion of an exogenous epitope into extra-membrane loops. - Teufel, M (1993)
Bacteriorhodopsin (BR) is folded into a bundle of seven alpha-helices which is embedded in the cellular membrane of Halobacterium salinarium; these helices are connected by short extra-membrane loops, three on the cytoplasmic side and three on the outside. Oligonucleotide-directed insertion or replacement mutagenesis was used to integrate the C-terminal sequence (13 amino acids long) of Sendai virus L-protein individually into each of the six helix-connecting loops. The altered gene products were obtained by expression of the mutant genes in either Escherichia coli or Schizosaccharomyces pombe and were used to reconstitute BR in proteoliposomes. In four cases (altered loops B/C, C/D, D/E or E/F), the mutant BRs were found to be fully functional as judged by light-driven proton pumping and photocycle kinetics. Within the four functional BR variants, recognition of the viral epitope by a monoclonal antibody is restricted to modified loops B/C and E/F. Immunogold staining of S.pombe cells producing either of the two latter BR variants shows that the protein is distributed among various cellular membranes but is not present in mitochondrial membranes. Sequence alteration of loop A/B or F/G resulted in loss of function, most plausibly due to a folding defect of the respective proteins. These results on the one hand document differences in structural importance of the various BR extra-membrane loops and on the other hand open the door to the construction of multifunctional membrane proteins via loop replacement mutagenesis of BR.